DETERMINASI KESADARAN WAJIB PAJAK, TINGKAT PENDIDIKAN DAN PENDAPATAN TERHADAP KEPATUHAN MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) DI DESA KEBONAGUNG DEMAK - Titik Rianawati; Arini Novandalina; Sabtarini Kusumaningsih (Jurnal Akuntansi dan Bisnis, 2025)
The purpose of this study is to analyze in depht how taxprayer awareness (X1), education level (X2), and income (X3) affect the level of community compliance in paying land and building taxes (Y) in Kebonagung Village, Demak. The population of this research is the people of Kebonagung village community, the sampling technique used is purposive sampling in the Kebonagung village community with a total of 100 people. This study uses an instrument in the form of a quesionnarire with a Likert scale as a measurement tool, and testing is done using SPSS. Meanwhile, the data testing techniques used in this study include validity tests, reliability tests, with Cronbach Alpha as a comparison. And to test and prove the research hypothesis, classical assumption tests and multiple linear regression analysis were used. The research results show that taxpayer awareness (X1), education level (X2), and income (X3) have an effect on compliance in paying land and building taxes (Y). Where the coefficient of determination (Adjusted R Square) value was obtained as 0.544, which means that the variables used in the research have an influence of 54.4%. To increase compliance in paying land and building tax, public awareness is needed in making payments, so there needs to be zocialization of laws and regulations related to taxation and the public needs to be aware that someone who already has their own income must be able to pay land and building tax